'What about the mother?' Women׳s and caregivers׳ perspectives on caesarean birth in a low-resource setting with rising caesarean section rates. Issue 7 (July 2015) - Litorp, Helena; Mgaya, Andrew; Kidanto, Hussein L.; Johnsdotter, Sara; Essén, Birgitta
Abstract Objective in light of the rising caesarean section rates in many developing countries, we sought to explore women׳s and caregivers׳ experiences, perceptions, attitudes, and beliefs in relation to caesarean section. Design qualitative study using semi-structured individual in-depth interviews, focus group discussions, and participant observations. The study relied on a framework of naturalistic inquiry and data were analysed using thematic analysis. Setting a public university hospital in Dar es Salaam, Tanzania. Participants we conducted a total of 29 individual interviews, 13 with women and 16 with caregivers, and two focus group discussions comprising five to six caregivers each. Women had undergone a caesarean section within two months preceding the interview and were interviewed in their homes. Caregivers were consultants, specialists, residents, and midwives. Findings both women and caregivers preferred vaginal birth, but caregivers also had a favourable attitude towards caesarean section. While caregivers emphasised their efforts to counsel women on caesarean section, women had often reacted with fear and shock to the caesarean section decision and perceived that there was a lack of indications. Although caesarean section was perceived as involving higher maternal risks than vaginal birth, both women and caregivers justified these risks by the need to 'secure' a healthy baby. Religious beliefs and community members seemed to influence women׳s caesarean section attitudes, which often made caregivers frustrated as it diminished their role as decision-makers. Undergoing caesarean section had negative socio-economic consequences for women and their families; however, caregivers seldom took these factors into account when making decisions. Key conclusions and implications for practice we raise a concern that women and caregivers might overlook maternal risks with caesarean section for the benefit of the baby, a shift in focus that can have serious consequences on women׳s health in low-resource settings. Caregivers need to reflect on how they counsel women on caesarean section, as many women perceived a lack of indication for their operations. Supportive attendance by a relative during birth and more comprehensive antenatal care counselling about caesarean section indications and complications might enhance women׳s autonomy and birth preparedness.